DEVELOPING MATERIAL FOR COMMUNICATIVE LANGUAGE TEACHING (CLT) TO TEACH ENGLISH FOR ECONOMICS STUDENTS - Aulia Hanifah Qomar; Ida Ayu Hani Erlina (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2017)
The objectives of this research are to develop materials for CLT as an interesting media to learn English grammar, to know how material in CLT works as a media to learn and evaluate English grammar facilitates students to learn more grammar and to know the responses from the students to the materials in CLT. This research is Research and Development (R&D) which use ADDIE design for the procedure. ADDIE design is stand for the procedure itself, these are Analyzing, Designing, Developing, Implementing and Evaluating. This research is designed by book material. The subject of this research is university students of Economic Faculty of Muhammadiyah University of Metro in the second semester. The instrument of this research is questionnaire. The questionnaire in this research is used to collect data which is divided into one aspects, is readability. The data is analyzed using Percentage Analysis Data. The data shows that the product is developed well. For the readability aspect, the result of expert is valid, one-to-one is valid, then in small group is increased to valid, and in the field test it is valid. Therefore, the product is developed well after each phase of the research. Based on the result of the research, the researcher concluds that the materials in CLT book can be learned attractively and interestingly. The students can understand the materials well. The learning process can be fun and comfortable for the students. The materials of CLT book media can be used in the class as a breakthrough of attractive and interactive learning which is very interesting for the students of earlier grade.